2017
DOI: 10.1177/0142331216688748
|View full text |Cite
|
Sign up to set email alerts
|

Real-time implementation of a maximum power point tracking algorithm based on first order sliding mode strategy for photovoltaic power systems

Abstract: This paper focuses on a maximum power point tracking (MPPT) algorithm based on the first order sliding mode approach. This work is aimed at systems that are fed with a photovoltaic (PV) generator. The main objective is to act on the panel to ensure that the energy collected is always at its maximum. Because a PV panel frequently suffers from non-linearity of its P-V curves, we propose to work with MPPT controllers based on the first order sliding mode approach; indeed, this approach in general is recognized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…It is desirable to use a nonlinear control technique to pursue MPP since PV systems exhibit nonlinear behavior. In this regard, several novel MPPT algorithms based on SMC have been implemented including current sensor based SMC [31], first order SMC [32], P&O based fractional SMC [33], INC based SMC [34], backstepping SMC [35], improved double integral SMC [36], fast terminal SMC-based direct power control [37], fuzzy neural network approach based terminal SMC [38], double integral SMC [39], second order SMC [40] , super twisting SMC [41], and PSO-based SMC [42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is desirable to use a nonlinear control technique to pursue MPP since PV systems exhibit nonlinear behavior. In this regard, several novel MPPT algorithms based on SMC have been implemented including current sensor based SMC [31], first order SMC [32], P&O based fractional SMC [33], INC based SMC [34], backstepping SMC [35], improved double integral SMC [36], fast terminal SMC-based direct power control [37], fuzzy neural network approach based terminal SMC [38], double integral SMC [39], second order SMC [40] , super twisting SMC [41], and PSO-based SMC [42].…”
Section: Introductionmentioning
confidence: 99%
“…Summarizing the literature on MPPT-based SMC above, it can be found that the first-order SMC-MPPTs [31], [32] have the qualities of being robust and straightforward, and they can be easily implemented in hardware. Nevertheless, they exhibit chattering issues and do not reveal good dynamics during rapid-changing environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The recharge time is improved by using the PV generator at its maximum power. For this goal, different MPPT algorithms are suggested in the literature: perturb and observe (P & O) [33][34][35], the incremental inductance (IC) [36][37][38], fuzzy logic (FL) [39][40][41], neuronal networks (NN) [42][43][44], particle swarm optimization (PSO) [45][46][47], and sliding mode [48,49] etc. High oscillation remains the major weakness of these MPPT approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Tracking the global peak of a PV module in any conditions is necessary to guarantee the maximum obtainable power. The MPP tracking (MPPT) is a non-linear control algorithm to tune the interfacing converter’s duty ratio continuously, so that it can draw maximum power from the solar arrays irrespective of load or weather conditions (Garraoui et al, 2017; Jiang et al, 2013; Lim and Hamil, 2000; Maity and Sahu, 2016). Over the last two decades, research on several MPPT methods using DC/DC converters has been reported in the literature (Enany et al, 2016; Esram and Chapman, 2007; Subudhi and Pradhan, 2013; Xiao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%